Empowering Women through the Role of the Village Head. - Anggraini, Ani Trianingsih; Agustina, Isna Fitria (Indonesian Journal of Public Policy Review, 2024)
A Qualitative Analysis" presents an investigation into the empowerment of women in Semambung Village, Kec. Wonoayu Kab. Sidoarjo. The research aims to describe and analyze the role of the Village Head in empowering women, utilizing qualitative methods such as observation, interviews, and documentation. The results indicate that the Village Head plays a significant role in women's empowerment through various dimensions, including entrepreneurship, disturbance handling, resource allocation, and negotiation. The implication of the study highlights the importance of the Village Head's involvement in empowering women at the local level, contributing to the overall welfare and development of the community. The title "Empowering Women: Unveiling the Role of Female Village Heads" encapsulates the essence of the study and its focus on the impactful role of female village heads in empowering women, making it appealing to a global audience of researchers and practitioners. Highlight : Entrepreneurship: The Village Head plays a significant role in empowering women through entrepreneurship, providing support and resources for women to start and grow their own businesses. Disturbance Handling: The Village Head's ability to handle disturbances and conflicts effectively contributes to a stable and supportive environment for women's empowerment. Resource Allocation: The Village Head's involvement in resource allocation ensures that resources are distributed fairly and effectively, contributing to the overall welfare and development of the community. Keywords: Women's Empowerment, Village Head, Entrepreneurship, Disturbance Handling, Resource Allocation